Social microblog TWITTER use to motivate young people (NEETs) to involve in distance education - Ratniece, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Across the world, young people face real and increasing difficulty in finding decent work with each passing day. Youth unemployment is not a new phenomenon; it is part of the global jobs crisis. Two additional emerging factors are worsening the youth employment crisis even further and causing challenges in the transition to decent work:  Increase in “discouraged youth”, in other words young people “neither in education nor in employment or training” (NEET).  Rising unemployment among university graduates, and more generally graduates of tertiary education institutions. What can be done to solve the dropout crisis with microblogging possibilities? Bloggers are driven to document their lives, provide commentary and opinions, express deeply felt emotions,articulate ideas through writing, and form andmaintain community forums. Using Twitter is becoming more relevant than ever, but we need to be aware of how any given audience engages with Twitter. Many educators have found that Twitter is a great tool to help increase participation and continue to engage students once they’ve left the classroom.The use of e-learning in itself does not constitute an enhancement of the quality of teaching and learning, but it is a potential enabler for such enhancement. Examples of actual good practice have been provided to illustrate how certain initiatives have addressed challenges and sought to engage learners in an effective manner.